An in-phase-coupled class-C quadrature VCO with tunable phase error - Zhang, Yuxiang (2015)
This letter presents the design and analysis of a novel in-phase-coupled (IPC) Class-C Quadrature Voltage-Controlled Oscillator (QVCO) with tunable phase error. The IPC QVCO employs a novel coupling structure that generates in-phase coupling signal while consuming negligible power itself. IPC scheme enables the QVCO to achieve better phase noise and phase error compared to that of the conventional QVCO. The phase error of the proposed IPC QVCO is also tunable. The proposed IPC QVCO is fabricated using 0.18 μm CMOS technology and the measured output frequency range is from 2.5 to 2.97 GHz. At 2.623 GHz, with 3.6 mW power consumption, the phase noise at 1 MHz offset achieves -126.8 dBc/Hz while the phase error before phase error tuning is 0.5 °. The measured phase error tuning range is ±17°.